2017
DOI: 10.3389/fnagi.2017.00182
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Psychological Symptoms Impact Clinical Competence in Alzheimer’s Disease

Abstract: Decision-making is considered a fundamental aspect of personal autonomy and can be affected in psychiatric and neurologic diseases. It has been shown that cognitive deficits in dementia impact negatively on decision-making. Moreover, studies highlighted impaired clinical competence in neuropsychiatric disorders, such as schizophrenia and bipolar disorder. In this context, the current study explored the relationship between behavioral and psychological symptoms of dementia (BPSD) and clinical competence, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 59 publications
0
32
0
3
Order By: Relevance
“…While the need for dependency and care is acknowledged, our participants felt it essential to balance it by preserving the autonomy of the PwD. While autonomy is an ethical construct that demands the highest advocacy, studies have reported that autonomy restriction can further increase the behavioral problems related to dementia ( 40 ). Some of the important factors leading to abuse according to our study could be poor knowledge about managing BPSD among the caregivers, caregiver burden, restriction of autonomy, and limitations of virtual consultations.…”
Section: Discussionmentioning
confidence: 90%
“…While the need for dependency and care is acknowledged, our participants felt it essential to balance it by preserving the autonomy of the PwD. While autonomy is an ethical construct that demands the highest advocacy, studies have reported that autonomy restriction can further increase the behavioral problems related to dementia ( 40 ). Some of the important factors leading to abuse according to our study could be poor knowledge about managing BPSD among the caregivers, caregiver burden, restriction of autonomy, and limitations of virtual consultations.…”
Section: Discussionmentioning
confidence: 90%
“…[4][5][6][7][8]36,37 Adverse effects of antipsychotics may counterpoise their benefits for the treatment of psychosis and agitation; 38 on the other hand, patients with stable BPSD symptoms under antipsychotics treatment may have better competence and more potential to improve in cognitive function. 39 In the current trial, around half of subjects (25/49 [51%] in the benzoate group; 22/48 [46%] in the placebo group) were receiving antipsychotics, 21 thereby perhaps reducing the potential of benzoate efficacy for not only psychotic symptoms but also cognitive impairment. Benzoate exerted antipsychotic properties in a mouse model 40 and in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, delusions may have a different impact on patients’ functioning than hallucinations or agitation. Bertrand and colleagues (Bertrand et al, 2017) found that patients with mild to moderate AD who had delusions had a decreased ability to express treatment choice preference, potentially impacting their ability to consent to medical care. In contrast, patients with hallucinations, agitation/aggression, and several other BPSD did not have weaknesses in decision-making abilities.…”
Section: Delusionsmentioning
confidence: 99%